Improving High School Students' Performance in Basic Calculus Using The Enhancing Mastery and Expertise in Mathematics Supplementary Material - Maria Merlinda A Nunez; Alberto D Yazon; Sherwin B Sapin; Victoria E Tamban; Karen A Manaig (Research Synergy Foundation, 2023)
Preparing K-12 students to gear up for higher mathematics and sciences, and to be more mathematically college-ready, teachers were given the essential role in bridging the learning gaps. One way to address this was the utilization of modules. The researcher developed Enhancing Mastery & Expertise in Mathematics (EM&EM) module in Basic Calculus. The objective of this quasi-experimental research was to evaluate the effectiveness of the EM&EM module in improving students' performance about the theorems of differentiation. The experimental and comparison groups comprised forty-six (46) Grade 11 students who used the EM&EM module and the DepEd module, respectively. The instruments used in the study were the pretest, formative tests, and posttest found in the EM&EM module. Mean and standard deviation were used to describe student performance in these assessments. To see if a significant difference existed, the formative test and posttest scores between the two groups were analyzed using an independent t-test, while the pretest and posttest scores within each group were analyzed using a paired sample t-test. The findings showed that the experimental and comparison groups' formative tests and posttest scores did not differ significantly, although the former generally performed better when their mean scores were compared. However, there was a significant difference between the two groups' pretest and posttest scores, and that had a large positive effect on their improvement. Therefore, just like the DepEd module, the EM&EM module was effective in facilitating the learning process. Overall, the EM&EM module significantly and substantially enhanced students' learning of Basic Calculus.